Association of fungi with dead Nzinga palmivora Wilson (Homoptera: Cicadellidae) in coconut plots in Ghana - R. N. Quaicoe; G. K. Yawson (International Coconut Community Journal, 2006)
Nzinga palmivora is one of the putative vectors of the Cape St. Paul Wilt Disease of coconut in Ghana. During a study to determine the seasonal population dynamics of the insect on coconut palms in the field, many of the insects were found dead and covered with fungal mycelia at one location. To investigate the role of the colonizing fungi in the death of the insects, two treatments of crude inocula, prepared from dead insects ground in sterile distilled water, were used to treat live insects in fyltis sleeve cages built around leaflets of coconut fronds. Insects treated with sterile distilled water (sdH2O) alone, served as the control. The insects treated with the crude inocula showed higher mortality compared with the control (p